Aplicación móvil basada en gamificación para apoyar la telerehabilitación física asíncrona - De La Cruz Gende, Luis Alfredo (2024)
This project addresses the need to support the rehabilitation process of people from their homes, especially in underdeveloped areas where access to therapeutic centers is limited. It must be taken into account that people with physical conditions that make their mobility difficult usually lack the motivation to continue their rehabilitation, which can have serious consequences on their daily life. To address this problem, a gamification-based mobile application for telerehabilitation is proposed. Meetings were held with specialists in the field to compile the requirements to be incorporated into the application. Subsequently, the usefulness of the application was evaluated through case studies. The application received good acceptance from users, who found the gamification approach interesting as it motivates them to perform rehabilitation exercises proposed by the therapist on a regular basis. Competition between users also turned out to be a motivating factor to maintain consistency in the exercises. This project demonstrates the potential of gamification-based telerehabilitation applications to motivate people to continue their recovery from their homes. Furthermore, it highlights the importance of developing accessible technologies for less advantaged areas, which can have a significant impact on the quality of life of people in these regions.